Comparison of CTP Score, MELD Na, and CLIF SOFA Score in Predicting Three Months Mortality in Cirrhotic Patients in a Tertiary Care Center - Jha, Anurag; Pathak, Rahul; Bhandari, Brindeswari Kafle; Hamal, Rabin; Sherpa, Tshering Wangdi; Koirala, Dinesh; Jha, Khusbu; Gyawali, Susmita (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Cirrhosis of liver is a major health problem in our country. With the development of decompensation there is an increased probability of mortality. CTP score, MELD Na, and CLIF SOFA score are used in predicting three months mortality in cirrhotic patients. We aim in evaluating the score which has the best results in our settings. METHODS 120 cirrhotic patients were admitted in the Department of Gastroenterology within one year for complications of cirrhosis. CTP score, MELD Na, and CLIF SOFA score were calculated. The performance of CTP score, MELD Na and CLIF SOFA score in predicting three-month mortality was analyzed by calculating the area under the receiver operating characteristics curves. RESULTS Among the 120 patients, there were 81 males and 39 females with age range of 18 to 76 years. Abdominal distension and jaundice combined was the most common presentation 41 (34.2%). Alcohol induced cirrhosis of liver comprised the majority of cases 90 (75%), followed by Hepatitis B virus induced cirrhosis 14 (11.7%). Acute-on-chronic liver failure was present in 39 (32.5%) patients. On 3 months follow up 56 (46.7%) patients had died. The area under the receiver operating characteristics for CTP score, MELD Na and CLIF SOFA score was 0.86, 0.88 and 0.91 respectively. CONCLUSIONS Cirrhosis of liver is one of the common presentations in our clinics with alcoholic cirrhosis being the most common in Nepal. Ascites, hepatic encephalopathy, impaired renal function and ACLF are independent predictors of mortality. CLIF SOFA score was more sensitive in predicting three months mortality as compared to CTP and MELD Na scores in our settings.